2015
DOI: 10.1136/sextrans-2015-052270.375
|View full text |Cite
|
Sign up to set email alerts
|

P08.29 Web-tool to assess the cost-effectiveness of chlamydia point-of-care tests at the local level

Abstract: Introduction There is a lack of data on the sexual behaviour of patients between being tested for chlamydia, receiving the test result, and being treated. This time-period may be important in the transmission of chlamydia, as infection could continue to be spread to sexual partners whilst awaiting the test result and treatment.We aimed to investigate the sexual behaviours of patients in this time-period in order to investigate the benefits a point-ofcare test (POCT) might bring to clinical practice. Methods A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Future research is required to evaluate its performance in different settings, as well as in male participants. Although previous modelling work has demonstrated that a CT-only POCT could have an epidemiological impact and be cost-saving at the local level ( Harding-Esch et al, 2015 ), dual CT/NG NAAT testing is most commonly employed in GUM/RSH settings in the UK. Therefore, further work is needed to assess the feasibility, acceptability and cost-effectiveness of POCTs for CT in GUM/RSH clinic settings ( Harding-Esch et al, 2017a ).…”
Section: Discussionmentioning
confidence: 99%
“…Future research is required to evaluate its performance in different settings, as well as in male participants. Although previous modelling work has demonstrated that a CT-only POCT could have an epidemiological impact and be cost-saving at the local level ( Harding-Esch et al, 2015 ), dual CT/NG NAAT testing is most commonly employed in GUM/RSH settings in the UK. Therefore, further work is needed to assess the feasibility, acceptability and cost-effectiveness of POCTs for CT in GUM/RSH clinic settings ( Harding-Esch et al, 2017a ).…”
Section: Discussionmentioning
confidence: 99%
“…Although previous modelling work has demonstrated that a CT-only POCT could have an epidemiological impact and be cost-saving at the local level 45 , dual CT/NG NAAT testing is most commonly employed in GUM/RSH settings in the UK. Therefore, further work is needed to assess the feasibility, acceptability and cost-effectiveness of a CT-only POCT in GUM/RSH clinic settings.…”
Section: Performance Evaluations For Us Food and Drug Administration mentioning
confidence: 99%